AKTIVITAS PENURUNAN KADAR GLUKOSA DARAH TIKUS PADA EKSTRAK DAUN LIDAH MERTUA (Sansevieria trifasciata Prain) - Utatik; Rifda Naufa Lina; Hasty Martha Wijaya (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2023)
Sansevieria trifasciata is one of the plants used as medicine, especially the leaves are used by the community as a lowering blood glucose. Flavonoid compounds contained in Sansevieria trifasciata’s leaves have antioxidant properties that protect pancreatic cells from free radicals. The purpose of this study was to determine the activity of the ethanol extract of Sansevieria trifasciata’s leaves in reducing blood glucose levels in rats. This research was conducted using the pre and post-test method with randomized control group design, using 5 treatment groups: negative control (CMC Na), positive control (Glibenclamide 0.09 mg/200 gBW) and 3 treatment groups with doses: 100, 150 and 200 mg/kgBB. All groups were induced with alloxan 150 mg/kgBW i.p for 3 consecutive days, then given treatment for 15 days. Data were analyzed statistically by ANOVA test with p <0.05 then followed by LSD test. The test results in this study showed that there was no significant difference between the positive controls at doses of 150 and 200 mg/kgBW with p>0.05. The highest activity was achieved by a dose of 200 mg/kgBW because it reduced blood glucose levels to the highest, namely 32.6 mg/dl on the 15th day.